Efecto de la proteína Ski sobre la susceptibilidad de células MCF-7 a la muerte inducida por docetaxel - Hinojosa S., Claudia; Jara V., Macarena; Diez U., Daniela; Marcelain C., Katherine (Revista Hospital Clínico Universidad de Chile, 2012)
Docetaxel, a drug used in advanced stages of breast cancer, induces stabilization of microtubules, inhibiting the process of cell division and consequently causes a special type of cell death called mitotic catastrophe. Recently it has been shown that the Ski protein, whenoverexpressed, induces mitotic catastrophe in Mouse Embryo Fibroblasts (MEFs). In this work, we evaluated the effect of Ski over expression on docetaxel-induced cell death in a breast cancer cell line, MCF-7. Cells overexpressing GFP (control) or GFP-Ski were incubated with 0-25-50-100 nM docetaxel for 72 hours. Cell death was evaluated by studying cellular and nuclear morphology by fluorescence microscopy. We found that at 25 nM, 50 nM and 100 nM, docetaxel induced an average of 77.93, 90.04 and 90.39% cell death in control cells; and 86.89, 83.54 and 87.22% in cells overexpressing Ski, respectively. No significant differences were found regarding drug concentrations or Ski over expression. However, under basal conditions (without docetaxel), over expression of Ski significantly induced mitotic catastrophe compared to control cells (22.04% vs. 2.38% cell death). This data support previous findingssuggesting that Ski participates in the activation of mitotic catastrophe in cells with mitotic defects, as a mechanism to preserve chromosom estability.